The level of local development and the need for local government investment indicated by residents of selected communes in the Lublin voivodeship - Komor, Agnieszka (Poziom rozwoju lokalnego a potrzeby w zakresie inwestycji samorządowych w opinii mieszkańców wybranych gmin województwa lubelskiego, 2020)
This paper aimed to identify and analyse the needs for local government investments indicated by respondents from selected communes of the Lublin voivodeship, depending on the level of socio-economic development of the analysed units. Research hypothesis H1, stating that there is a relationship between the level of local development and the need for local government investment indicated by respondents, was corroborated. The research covered 16 communes. The research period was in general the year of 2018 (in the absence of data, the latest available information was used). The surveys showed there was an average correlation between the local development level and the need for local authorities to create green areas, tourist infrastructure and expenditure on the development of investment land. An average negative correlation between the level of local development and the need for investing in roads and pavements was also identified. This indicates a partial confirmation of hypothesis H1
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 8, s. 40-53